Potential of ethanolic extracts from seed kernel Indonesian cultivars mangoes as an anti-multidrug-resistant (MDR) Escherichia coli - Tulus Ariyadi; Sitti Qayimah; Lulu’ Nur Assa’diyah; Asyiah Asyiah; Hanum Adisty Pratiwi; Afifah Khairunnisa; Annisa Nurul Hikmah; Lia Kusmita; Mutmainah Mutmainah; Ana Hidayati Mukaromah (JURNAL INDONESIA DARI ILMU LABORATORIUM MEDIS DAN TEKNOLOGI, 2025)
Escherichia coli is a type of bacteria that often found in wound infections. The use of antibiotics to treat these uncontrolled infections has resulted in the emergence of multi-drug resistant (MDR) strains of pathogenic bacteria.  This rapid increase in MDR E. coli strains has led to significant morbidity and mortality in human populations. Consequently, the exploration of natural antibacterial agents is urgently needed. One promising resource is mango extract, which is recognised for its antibacterial properties and is obtained through solvent extraction using 96% ethanol. This study aimed to determine the antibacterial activity of seed extracts from seven different mango cultivars (Mangifera indica L.), against MDR E. coli. The study focused on determining the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) using dilution method. The concentrations examined for both MIC and MBC were 5, 10, 50, and 100 mg/mL. The results indicate that the mango seed extract exhibit significant antibacterial activity against MDR-E. coli., with the kweni cultivar showing the largest inhibition zone measuring 23.25 mm. The ethanol extract from the kweni seeds yielded the most favorable results, with an MIC value of ≥0.078 mg/mL and an MBC value that ranged from 1.25-10 mg/mL. In conclusion, mango seed extract, particularly from the kweni cultivar, has substantial potential to be developed as an effective antibacterial agent against MDR-E. coli.